Increasing apple productivity through high-density planting - Srivastava, K K; Kumar, Dinesh; Singh, D B; Singh, S R; Mir, J I; Sharma, O C (Indian Horticulture, 2019)
High-density planting system which accommodates more number of plants per unit area, can sustain the modern tool of plant architecture management which include training, pruning and canopy orientation. The high-density orcharding offers good scope for higher apple productivity per unit area and use of modern scientific concept of plant architectural engineering.